Analysis of the Effect of Marketing Mix (4p) on Purchase Decisions Fashion Products on Shopee's E-commerce (Case study on the Z Generation of the City of Surakarta) - Susi Anggi Purnama Sari; Kusdiyanto Kusdiyanto (Proceedings Series on Social Sciences & Humanities, 2024)
This study examines the analysis of the influence of a marketing mix (4p) on the purchase decision of a fashion product on Shopee's E-commerce (a case study on the Z-generation of the city of Surakarta). Marketing mix (4P) is the Product, Price, Promotion, and Place. The study aims to analyze whether the marketing mix (4p) influences the purchase of fashion products on the e-commerce Shopee made by the Generation Z. In accordance with the phenomenon that we raise that fashion shopping phenomena in Generation Z are highly supported by the existing data. This study used a quantitative research method because the population of this study cannot be generalized with certainty, sampling using a non-probability sampler approach. The study uses a sample of 151 generations of Surakarta city Z that have been confirmed and are qualified for testing because they have passed the data verification phase. Where data is measured numerically and using Structural Equation Modeling (SEM) with Partial Least Square (PLS) via Smart-PLS 3.0 software. The result is Price, Promotion, and Places have a significant positive influence on Shopee's E-Commerce Fashion Product Purchase Decision. Whereas the Product significantly has a negative impact on the Shopee E-commerce Fashion Products Purchasing Decision The conclusion of this study is that 3 variables are significantly influenced by the purchasing decision and 1 negative variable is not significant to the purchase decision so that it can be used as a basis forining the related strategy. This will have a greater impact on the sales and turnover of the company's profits.